Exploring the Influencing Paths of Villagers’ Participation in the Creation of Micro-Landscapes: An Integrative Model of Theory of Planned Behavior and Norm Activation Theory - Cheng, Huishan; Rui, Quanquan; Yu, Kunyong; Li, Xiaohe; Liu, Jian (Frontiers in Psychology, 2022)
The villager participation has become a key breakthrough in the predicament of rural landscape governance. With planned behavior theory and normative activation theory as the framework, this study adopts the structural equation model to explore the influencing mechanism of villager participation in rural micro-landscape based on the research data of totally 574 villagers in Jinjiang rural micro-landscape construction survey. The results indicate that: (1) Integrated planned behavior and normative activation theory can better explain the influencing mechanism of villager participation in rural micro-landscape construction; (2) Perception dimension, norm dimension, attitude dimension and control dimension all produce significant influence on participation behavior intention, with the degree of effect sequenced by attitude dimension (0.635)＞norm dimension (0.557)＞control dimension (0.407)＞perception dimension (0.401); (3) According to the mediation results, it can be found that natural environment perception, social environment perception, personal norm, social norm, participation attitude, result awareness and self-efficacy all exert indirect effect on participation behavior based on villager participation behavioral intention, with the degree of mediation effect intensity as result awareness (0.611)＞personal norm (0.53)＞ participation attitude (0.415)＞natural environment awareness (0.361)＞self-efficacy (0.344)＞ social environment awareness (0.272)＞social norm (0.332).